Composite film material for energy storage capacitor and preparation method and application thereof

By using composite film materials of polyvinylidene fluoride and barium titanate @ polydopamine filler in energy storage capacitors, the problems of increased dielectric loss and decreased breakdown field strength in PVDF materials are solved, and efficient electrical branch cutoff and storage are achieved Energy density is increased.

CN119431976AInactive Publication Date: 2025-02-14CHANGZHOU INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411566036.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polyvinylidene fluoride (PVDF) in energy storage capacitors increases dielectric loss and decreases in breakdown field strength due to ferroelectric polarization and high dielectric ceramic fillers. The rapid development of electrical branches leads to premature breakdown of materials.

Method used

The composite film material of polyvinylidene fluoride and barium titanate @ polydopamine filler is made of core-shell structure, the core is barium titanate and the shell is polydopamine, which is prepared by oxidative polymerization cross-linking reaction, volume The fraction is 3 to 10%, the polydopamine layer is in amorphous state, and has good compatibility and bonding properties with polyvinylidene fluoride.

Benefits of technology

It has achieved a good cutoff effect on electric branches, and the release energy density is increased by 191-304%, which has significantly improved the energy storage performance and service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431976A_ABST
    Figure CN119431976A_ABST
Patent Text Reader

Abstract

The invention provides a composite film material for an energy storage capacitor and a preparation method and application thereof, and belongs to the field of polymer composite materials. The invention provides a thin film. The thin film comprises polyvinylidene fluoride and a barium titanate and polydopamine filler dispersed in the polyvinylidene fluoride, the barium titanate and polydopamine filler is of a core-shell structure, the core is barium titanate, and the shell is polydopamine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polymer composite materials, and in particular to a composite film material for energy storage capacitors, a preparation method thereof and applications thereof. Background Art

[0002] As a key energy storage material for film capacitors, the electrical performance technical indicators of polymers play a decisive role in the energy storage and performance of capacitors, especially the dielectric constant, breakdown field strength, energy storage density and other indicators of film materials.

[0003] In theory, polyvinylidene fluoride (PVDF) is very beneficial to improve the energy storage density of polymer materials. However, the intrinsic ferroelectric polarization of PVDF and the high dielectric ceramic filler bring greater dielectric polarization, which in turn causes a sharp increase in dielectric loss and a decrease in breakdown field strength of PVDF and ceramic composite materials. This is due to the reduced insulation caused by the internal electron transport of the material, which causes the electrical tree to develop too quickly and cause premature breakdown of the material. Summary of the invention

[0004] The invention provides a composite film material for energy storage capacitors, a preparation method and an application thereof. The single-layer film of the invention has a good cutting effect on electrical tree branches.

[0005] The invention provides a film, comprising polyvinylidene fluoride and barium titanate@polydopamine filler dispersed in the polyvinylidene fluoride; the barium titanate@polydopamine filler is a core-shell structure, the core is barium titanate, and the shell is polydopamine.

[0006] The polydopamine layer is amorphous, and has a large number of functional groups such as amino and hydroxyl groups on its surface. It has good compatibility with polyvinylidene fluoride (i.e., strong bonding), and can easily combine polyvinylidene fluoride and barium titanate tightly through hydrogen bonds and other bonding effects with polyvinylidene fluoride to improve the cutting effect on electrical dendrites.

[0007] The PMMA film in the composite film of the present invention has a good absorption effect on the electrical tree branches, and the strong combination of polyvinylidene fluoride and barium titanate@polydopamine filler in the film has a good synergistic effect on the cutting effect of the electrical tree branches, resulting in a release energy density of up to 9.7-13.5 J / cm 3 , which is 191-304% higher than pure polyvinylidene fluoride substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 XRD pattern of BT@D nanoparticles obtained in Example 1;

[0009] Figure 2 TEM image and local magnified image of BT@D nanoparticles obtained in Example 1;

[0010] Figure 3This is a comparison chart of infrared spectra of barium titanate (BT) nanoparticles obtained in step (1) c of Example 1 and BT@D nanoparticles obtained in Example 1;

[0011] Figure 4 XRD comparison diagram of the BP composite films obtained in Comparative Examples 2 to 5;

[0012] Figure 5 XRD comparison diagram of the BDP composite films obtained in Examples 2 to 5;

[0013] Figure 6 The SEM images of the BP composite films obtained in Comparative Examples 3 to 5 and the BDP composite films obtained in Examples 3 to 5;

[0014] Figure 7 The dielectric constant and dielectric loss comparison diagram of the BP composite films obtained in Comparative Examples 2 to 5;

[0015] Figure 8 A comparison diagram of the dielectric constant and dielectric loss of the BDP composite films obtained in Examples 2 to 5;

[0016] Fig. 9 The SEM images of the composite films obtained in Example 6 and Comparative Example 6;

[0017] Fig.10 The dielectric constant and dielectric loss comparison diagram of the PVDF film obtained in Comparative Example 1, Example 4, Example 6 and the composite film obtained in Comparative Example 6;

[0018] Fig.11 It is a comparison diagram of the leakage current density of the PVDF film obtained in Comparative Example 1, Example 4, Example 6 and the composite film obtained in Comparative Example 6;

[0019] Fig.12 A comparison diagram of the breakdown field strength Weibull distribution of the PVDF film obtained in Comparative Example 1, Example 4, Example 6, and the composite film obtained in Comparative Example 6;

[0020] Fig.13 This is a simulation diagram of electrical dendrites of the BP composite film obtained in Comparative Example 4;

[0021] Fig.14 This is a simulation diagram of electrical dendrites of the BDP composite film obtained in Example 4;

[0022] Fig.15 This is a simulation diagram of electrical dendrites of the composite film obtained in Example 6;

[0023] Fig.16 It is a comparison diagram of the difference between the maximum electric displacement polarization value Dm and the residual polarization value Dr of the PVDF film obtained in Comparative Example 1, Example 4, Example 6 and the composite film obtained in Comparative Example 6;

[0024] Fig.17 It is a comparison chart of the released energy density and the charge-discharge efficiency of the PVDF film obtained in Comparative Example 1, Example 4, Example 6 and the composite film obtained in Comparative Example 6. DETAILED DESCRIPTION

[0025] The present invention provides a film, comprising polyvinylidene fluoride and barium titanate@polydopamine filler dispersed in the polyvinylidene fluoride;

[0026] The barium titanate@polydopamine filler is a core-shell structure, wherein the core is barium titanate and the shell is polydopamine.

[0027] In the present invention, the volume fraction of barium titanate@polydopamine filler in the film is preferably 3-10%, and the volume fraction can be 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%; the thickness of polydopamine in the barium titanate@polydopamine filler is preferably 2-10nm, and the thickness can be 2nm, 4nm, 6nm, 8nm or 10nm; the particle size of barium titanate is preferably below 100nm, and the particle size can be 20nm, 40nm, 60nm, 80nm or 100nm.

[0028] In the present invention, the preparation method of the barium titanate@polydopamine filler preferably comprises the following steps:

[0029] Barium titanate, an aqueous solution of Tris-hydrochloric acid and dopamine hydrochloride are mixed to carry out an oxidative polymerization cross-linking reaction to obtain the barium titanate@polydopamine filler.

[0030] In the present invention, the mixing preferably includes first mixing barium titanate with an aqueous solution of Tris-hydrochloric acid to obtain a first mixture; and second mixing the first mixture with dopamine hydrochloride to cause an oxidative polymerization cross-linking reaction.

[0031] In the present invention, the solid-to-liquid ratio of the aqueous solution of barium titanate and Tris-hydrochloric acid is preferably 0.22-0.27 g:200 mL.

[0032] In the present invention, the preparation method of barium titanate preferably comprises the following steps:

[0033] The barium titanate raw material is wet ball-milled and then dried.

[0034] In the present invention, the wet ball milling time is preferably 4 to 6 hours, and the time can be 4 hours, 5 hours or 6 hours; the solvent used for the wet ball milling is preferably ethanol; the rotation speed of the wet ball milling is preferably 600 to 800 r / min, and the rotation speed can be 600 r / min, 650 r / min, 700 r / min, 750 r / min or 800 r / min.

[0035] In the present invention, the drying temperature is preferably 60-80°C, and the temperature can be 60°C, 65°C, 70°C, 75°C or 80°C; the drying time is preferably 10-14h, and the time can be 10h, 11h, 12h, 13h or 14h.

[0036] The drying process removes the solvent used in the wet ball milling.

[0037] In the present invention, the pH value of the Tris-hydrochloric acid aqueous solution is preferably 8.2-8.8, and the pH value may be 8.2, 8.3, 8.4, 8.5, 8.6, 8.7 or 8.8; the concentration of Tris in the Tris-hydrochloric acid aqueous solution is preferably 9-11 mol / L, and the concentration may be 9 mol / L, 10 mol / L or 11 mol / L.

[0038] In the present invention, the method for preparing the aqueous solution of Tris-hydrochloric acid preferably comprises the following steps:

[0039] Dissolve Tris in water to obtain a Tris solution;

[0040] The diluted hydrochloric acid is mixed with the Tris solution for a third time to obtain the Tris-hydrochloric acid aqueous solution.

[0041] In the present invention, the third mixing preferably comprises dropping dilute hydrochloric acid into the Tris solution.

[0042] In the present invention, the mass fraction of the dilute hydrochloric acid is preferably 16-20%, and the mass fraction can be 16%, 17%, 18%, 19% or 20%.

[0043] In the present invention, the dropping is preferably carried out under the condition of magnetic stirring, and the time of the magnetic stirring is preferably 5 to 15 minutes, and the time can be 5 minutes, 8 minutes, 10 minutes, 12 minutes or 15 minutes; the rotation speed of the magnetic stirring is preferably 80 to 120 r / min, and the speed can be 80 r / min, 90 r / min, 100 r / min, 110 r / min or 120 r / min.

[0044] In the present invention, the first mixing preferably includes cyclic ultrasonic mixing and first magnetic stirring mixing, and second magnetic stirring mixing after the cycle is completed; in the present invention, the number of cycles is preferably 3 to 5 times, and the number of cycles can be 3 times, 4 times or 5 times; in each cycle, the power of the ultrasonic mixing is preferably independently 150 to 250 W, and in each cycle, the power can be independently 150 W, 180 W, 200 W, 220 W or 250 W; in each cycle, the time of the ultrasonic mixing is preferably independently 10 to 20 min, and in each cycle, the time can be independently The first magnetic stirring mixing time is preferably 10 to 20 minutes, and the first time can be independently 10 minutes, 12 minutes, 15 minutes, 18 minutes or 20 minutes in each cycle; in each cycle, the rotation speed of the first magnetic stirring mixing is preferably 80 to 160 r / min, and in each cycle, the rotation speed can be 80 r / min, 100 r / min, 120 r / min, 140 r / min or 160 r / min; in each cycle, the first magnetic stirring mixing time is preferably 10 to 20 minutes, and in each cycle, the first time can be independently 10 minutes, 12 minutes, 15 minutes, 18 minutes or 20 minutes.

[0045] In the present invention, the rotation speed of the second magnetic stirring mixing is preferably 80-160r / min, and the rotation speed can be 80r / min, 100r / min, 120r / min, 140r / min or 160r / min; the time of the second magnetic stirring mixing is preferably 10-14h, and the time can be 10h, 11h, 12h, 13h or 14h.

[0046] In the present invention, the mass ratio of Tris to dopamine hydrochloride is preferably 1:0.125-0.375, and the mass ratio may be 1:0.125, 1:0.15, 1:0.2, 1:0.25, 1:0.3 or 1:0.375.

[0047] In the present invention, the second mixing is preferably carried out under magnetic stirring conditions, the rotation speed of the magnetic stirring is preferably 100-300 r / min, and the rotation speed may be 100 r / min, 150 r / min, 200 r / min, 250 r / min or 300 r / min; the rotation speed of the magnetic stirring is preferably 10-20 h, and the time may be 10 h, 12 h, 14 h, 16 h, 18 h or 20 h.

[0048] An oxidative polymerization cross-linking reaction occurs in the second mixing.

[0049] After the second mixing is completed, the present invention preferably performs solid-liquid separation on the obtained product, and then washes, dries and grinds the obtained solid.

[0050] In the present invention, the washing preferably includes repeated washing with water; the number of repeated washings is preferably 3 to 5 times.

[0051] In the present invention, the drying temperature is preferably 60-80°C, and the drying temperature can be 60°C, 70°C or 80°C; the drying time is preferably 10-14h, and the drying time can be 10h, 11h, 12h, 13h or 14h.

[0052] In the present invention, the grinding time is preferably 1 to 2 hours.

[0053] The present invention also provides a method for preparing the film described in the above technical solution, comprising the following steps:

[0054] The polyvinylidene fluoride solution is mixed with the dispersion of barium titanate@polydopamine filler (referred to as the fourth mixing) and then coated and dried.

[0055] In the present invention, the method for preparing the polyvinylidene fluoride solution preferably comprises the following steps:

[0056] The polyvinylidene fluoride and the polar organic solvent are mixed, vacuumized, sealed and allowed to stand.

[0057] In the present invention, the fifth mixing preferably includes adding polyvinylidene fluoride to the polar organic solvent.

[0058] In the present invention, the solid-liquid ratio of the polyvinylidene fluoride to the polar organic solvent is preferably 1g:4-7.5mL, and the solid-liquid ratio can be 1g:4-7.5mL, 1g:4-4.5mL, 1g:4-5mL, 1g:4-5.5mL, 1g:4-6mL, 1g:4-6.5mL, 1g:4-7mL or 1g:4-7.5mL; the polar organic solvent preferably includes N,N-dimethylformamide

[0059] In the present invention, the adding is preferably carried out under the condition of magnetic stirring, the rotation speed of the magnetic stirring is preferably 300-400r / min, and the rotation speed of the magnetic stirring can be 300r / min, 350r / min or 400r / min; the time of the magnetic stirring is preferably 2-4h, and the time can be 2h, 3h or 4h.

[0060] In the present invention, the time of the vacuum treatment is preferably 0.5 to 1.5 h, and the time of the vacuum treatment can be 0.5 h, 1 h or 1.5 h.

[0061] In the present invention, the sealed standing time is preferably 1 to 3 hours, and the sealed standing time can be 1 hour, 2 hours or 3 hours.

[0062] In the present invention, the method for preparing the dispersion of barium titanate@polydopamine filler preferably comprises the following steps:

[0063] The barium titanate@polydopamine filler is dispersed in a polar organic solvent.

[0064] In the present invention, the solid-liquid ratio of the barium titanate @ polydopamine to the polar organic solvent is preferably 1 g: 7 to 35.5 mL, and the solid-liquid ratio may be 0.31 g: 9 to 11 mL, 0.53 g: 9 to 11 mL, 0.76 g: 9 to 11 mL or 1.13 g: 9 to 11 mL; the polar organic solvent preferably includes N, N-dimethylformamide.

[0065] In the present invention, the dispersion is preferably carried out in cyclic ultrasound and magnetic stirring. In the present invention, the number of cycles is preferably 3 to 5 times, and the number of cycles can be 3, 4 or 5 times; in each cycle, the power of the ultrasound is preferably independently 150 to 250 W, and in each cycle, the power of the ultrasound can be 150 W, 180 W, 200 W, 200 W or 250 W; in each cycle, the time of the ultrasound is preferably independently 10 to 20 min, and in each cycle, the time of the ultrasound can be 10 min, 12 min, 15 min, 18 min or 20 min. In the present invention, in each cycle, the speed of the magnetic stirring is preferably independently 80 to 160 r / min, and in each cycle, the speed of the magnetic stirring may be 80 r / min, 100 r / min, 120 r / min, 140 r / min or 160 r / min; in each cycle, the time of the magnetic stirring is preferably independently 10 to 20 min, and in each cycle, the time of the magnetic stirring may be 10 min, 12 min, 15 min, 18 min or 20 min.

[0066] In the present invention, the fourth mixing preferably includes adding the polyvinylidene fluoride solution into the dispersion of the barium titanate@polydopamine filler and then performing vacuum treatment and sealing and standing.

[0067] In the present invention, the volume ratio of polyvinylidene fluoride in the polyvinylidene fluoride solution to the barium titanate @ polydopamine filler in the dispersion of barium titanate @ polydopamine filler is preferably 9 to 32.3:1, and the volume ratio is preferably 9:1, 13.3:1, 19:1 or 32.3:1.

[0068] In the present invention, the addition speed is preferably 0.2-0.5 mL / min, and the addition speed can be 0.2 mL / min, 0.3 mL / min, 0.4 mL / min or 0.5 mLmg / min; the addition is preferably carried out under the condition of magnetic stirring, and the rotation speed of the magnetic stirring is preferably 400-600 r / min, and the rotation speed of the magnetic stirring can be 400 r / min, 450 r / min, 500 r / min, 550 r / min or 600 r / min; the time of the magnetic stirring is preferably 4-8 h, and the time of the magnetic stirring can be 4 h, 5 h, 6 h, 7 h or 8 h.

[0069] In the present invention, the time of the vacuum treatment is preferably 0.5 to 1.5 h, and the time of the vacuum treatment can be 0.5 h, 1 h or 1.5 h.

[0070] In the present invention, the sealed standing time is preferably 10 to 14 hours, and the sealed standing time can be 10 hours, 11 hours, 12 hours, 13 hours or 14 hours.

[0071] In the present invention, the drying temperature is preferably 50-70°C, and the temperature can be 50°C, 60°C or 70°C; the drying time is preferably 3-8 minutes, and the drying time can be 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes or 8 minutes;

[0072] After the drying, the present invention preferably cools the obtained dry film to room temperature.

[0073] After the cooling, the present invention preferably further dries the obtained film; the drying temperature is preferably 60-80°C, and the temperature can be 60°C, 70°C or 80°C; the drying time is preferably 20-26h, and the time can be 20h, 21h, 22h, 23h, 24h, 25h or 26h.

[0074] The present invention also provides a composite film, comprising a first PMMA film, a film and a second PMMA film stacked in sequence, wherein the film is the film described in the above technical solution or a film prepared by the preparation method described in the above technical solution.

[0075] In the present invention, the thickness of the first PMMA film, the film and the second PMMA film is preferably independently 9 to 11 μm, and the thickness of the first PMMA film, the film and the second PMMA film can be independently 9 μm, 10 μm or 11 μm. 。

[0076] In the present invention, the method for preparing the composite film preferably comprises the following steps:

[0077] Performing a first coating and a first drying on the first PMMA solution to form a first PMMA film;

[0078] The polyvinylidene fluoride solution is mixed with the dispersion of barium titanate@polydopamine filler (referred to as the fourth mixing), and then coated and dried on the first PMMA film to form a thin film;

[0079] A second methyl methacrylate solution is second-coated and second-dried on the film to form a second PMMA film, thereby obtaining the composite film.

[0080] In the present invention, the method for preparing the first PMMA solution preferably comprises the following steps:

[0081] After the PMMA and the polar organic solvent are mixed for the sixth time, the mixture is sealed and allowed to stand.

[0082] In the present invention, the solid-liquid ratio of PMMA to the polar organic solvent is preferably 1g:4-18mL, and the solid-liquid ratio may be 1g:4-18mL, 1g:6mL, 1g:8mL, 1g:10mL, 1g:12mL, 1g:14mL, 1g:16mL or 1g:18mL.

[0083] In the present invention, the sixth mixing is preferably carried out under the condition of magnetic stirring, the speed of the magnetic stirring is preferably 300-400r / min, and the speed of the magnetic stirring can be 300r / min, 350r / min or 400r / min; the time of the magnetic stirring is preferably 4-8h, and the time of the magnetic stirring can be 4h, 5h, 6h, 7h or 8h

[0084] In the present invention, the sealed standing time is preferably 1 to 3 hours, and the sealed standing time can be 1 hour, 2 hours or 3 hours.

[0085] In the present invention, the first drying temperature is preferably 50-70°C, and the first drying temperature can be 50°C, 60°C or 70°C; the time is preferably 3-8 min, and the first drying time can be 3 min, 4 min, 5 min, 6 min, 7 min or 8 min.

[0086] After the first drying, the present invention preferably cools the obtained dry film to room temperature to form a first PMMA film;

[0087] The raw material of the thin film is coated and dried on the first PMMA film to form a thin film.

[0088] The method for preparing the film has been discussed previously and will not be repeated here.

[0089] After the thin film is formed, the present invention performs a second coating and a second drying on a second methyl methacrylate solution on the thin film to form a second PMMA film.

[0090] The second methyl methacrylate solution, second coating and second drying are preferably independently consistent with the first methyl methacrylate solution, first coating and first drying.

[0091] After the second drying, the present invention preferably performs a third drying on the obtained composite film to obtain the composite thin film.

[0092] In the present invention, the temperature of the third drying is preferably 60-80°C, and the temperature of the third drying can be 60°C, 70°C or 80°C; the time is preferably 20-26h, and the time of the third drying can be 20h, 21h, 22h, 23h, 24h, 25h or 26h.

[0093] The composite film material for energy storage capacitors provided by the present invention, its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0094] PMMA (CAS NO 9011-14-7, No.: P141444) - Shanghai Aladdin Biotechnology Co., Ltd.;

[0095] Polyvinylidene fluoride (model FR904) - Shanghai Sanaifu New Material Technology Co., Ltd.

[0096] Example 1

[0097] (1) Preparation of BT@D

[0098] a. Mix 0.24 g Tris and 200 mL deionized water to prepare solution A;

[0099] Add 18% dilute hydrochloric acid to liquid A, stir magnetically for 10 min at a speed of 100 r / min, adjust the pH to 8.5, and prepare a Tris-hydrochloric acid aqueous solution B with a Tris concentration of 10 mmol / L;

[0100] c. The barium titanate nanoparticles were ball-milled for 5 h, the solvent was ethanol, the rotation speed was 700 r / min, and the liquid after ball milling was dried at 70° C. for 12 h to obtain barium titanate particles C with a particle size of 80 nm;

[0101] d. Add 1.5 g of barium titanate nanoparticles C to the above solution B, and perform cyclic treatment with ultrasound and magnetic stirring, with an ultrasound power of 200 W, an ultrasound time of 15 min, a magnetic stirring speed of 120 r / min, and a stirring time of 15 min. After 4 cycles, continue magnetic stirring for 12 h to obtain solution D.

[0102] e. Add 0.1 g of dopamine hydrochloride to solution D, and stir magnetically for 12 h at a stirring speed of 200 r / min to obtain a reaction solution E;

[0103] f. Pour off the supernatant in solution E and wash repeatedly with deionized water for 4 times;

[0104] g The cleaned powder was dried at 80° C. for 12 h, and then ground for 1 h to obtain barium titanate@polydopamine core-shell structure nanoparticle filler F (labeled as BT@D), whose polydopamine coating layer thickness was 2 nm.

[0105] The BT@D obtained in Example 1 was subjected to XRD analysis, and the results were as follows: Figure 1 shown.

[0106] Depend on Figure 1 It can be seen that in the range of 2 times the diffraction angle of 10 to 90°, typical diffraction peaks of (100), (110), (111), (200), (210), (211), (220), (300), (310), (311), and (222) crystal planes appear, indicating that the BT@D particles are completely crystallized and free of impurities, and are typical perovskite barium titanate crystals.

[0107] The BT@D obtained in Example 1 was subjected to TEM analysis and local amplification, and the results are as follows: Figure 2 shown.

[0108] Depend on Figure 2 It can be seen that the core of the BT@D particle is a spherical BT particle with a diameter of about 80nm; and the amorphous shell D is coated on the BT core particle to form a core-shell structured BT@D particle with a shell thickness of about 2nm.

[0109] The barium titanate nanoparticles obtained in step (1) c and the BT@D nanoparticles of Example 1 were subjected to infrared spectroscopy analysis. The results are as follows: Figure 3 shown.

[0110] Depend on Figure 3 It can be seen that after BT particles were treated with dopamine, the -1 A strong benzene ring vibration absorption peak appears at 2976cm -1 The typical CH vibration absorption peak appears at 3431 cm -1 A hydroxyl OH bond vibration absorption peak appears at , indicating that the BT and BT@D nanoparticles obtained in Example 1 have hydroxyl groups on their surfaces and have greater surface activity.

[0111] Example 2

[0112] (1) Same as step (1) of Example 1

[0113] (2) Solution preparation

[0114] a. Under magnetic stirring, slowly add 2 g of polyvinylidene fluoride powder into a conical flask containing 14 mL of N,N-dimethylformamide solvent, stir magnetically for 3 h at a stirring speed of 350 r / min, then evacuate for 1 h, seal and let stand for 2 h to obtain PVDF solution H;

[0115] b. Add 0.31 g BT@D into a conical flask containing 10 mL of N,N-dimethylformamide solvent, and perform cyclic treatment of power ultrasound and magnetic stirring. The ultrasound power is 200 W, the ultrasound time is 15 min, the magnetic stirring speed is 100 r / min, and the stirring time is 15 min. After 4 cycles, a mixed solution I is obtained.

[0116] c. Slowly add 14 mL of solution H to 10 mL of solution I (the volume ratio of polyvinylidene fluoride in solution H to BT@D filler F in solution I is 32.3:1), while keeping solution I in a magnetic stirring state, the addition rate is 0.3 mL / min, magnetic stirring is performed for 6 h, the stirring rate is 500 r / min, and then vacuum treatment is performed for 1 h, and sealed and allowed to stand for 12 h to obtain polyvinylidene fluoride filler interlayer mixed solution J;

[0117] (3) Single-layer composite film

[0118] The interlayer mixed solution J in step (2) was coated (film thickness was 11 μm) on a clean glass plate, dried at 60°C for 5 min and cooled to room temperature, and then dried at 80°C for 24 h to obtain a single-layer composite film (recorded as 3 vol.% BDP).

[0119] Example 3

[0120] The only difference from Example 2 is that the amount of BT@D used in step (2)b is 0.53 g, that is, the volume ratio of polyvinylidene fluoride in solution H to BT@D filler F in solution I is 19:1.

[0121] The single-layer composite film was recorded as 5 vol.% BDP.

[0122] Example 4

[0123] The only difference from Example 2 is that the amount of BT@D used in step (2)b is 0.76 g, that is, the volume ratio of polyvinylidene fluoride in solution H to BT@D filler F in solution I is 13.3:1.

[0124] The single-layer composite film was recorded as 7 vol. % BDP.

[0125] Example 5

[0126] The only difference from Example 2 is that the amount of BT@D used in step (2)b is 1.13 g, that is, the volume ratio of polyvinylidene fluoride in solution H to BT@D filler F in solution I is 9:1.

[0127] The single-layer composite film was recorded as 10 vol. % BDP.

[0128] Example 6

[0129] (1) Same as step (1) in Example 1.

[0130] (2) Solution preparation

[0131] 3 g of PMMA was added to 18 mL of N,N-dimethylformamide solvent, and magnetically stirred for 6 h at a stirring speed of 350 r / min. After complete dissolution, the solution was sealed and allowed to stand for 2 h to obtain a PMMA outer layer solution G.

[0132] Solutions H, I, and J are the same as those in Example 2.

[0133] (3) Three-layer composite film

[0134] a. Apply the outer layer solution G (film thickness 11 μm) on a clean glass plate and dry it at 60°C for 5 min, cool it to room temperature, apply the interlayer mixed solution J obtained in Example 4 (film thickness 11 μm), dry it at 60°C for 5 min and cool it to room temperature, then apply the outer layer solution G (film thickness 11 μm) and dry it at 60°C for 5 min;

[0135] b. Dry the three-layer film and the glass plate in the previous step at 80°C for 24 hours to obtain a three-layer composite film (PMMA-BDP-PMMA) with a thickness of 30 μm.

[0136] Comparative Example 1

[0137] Under magnetic stirring, 2 g of polyvinylidene fluoride powder was slowly added to 14 mL of N,N-dimethylformamide solvent, and magnetic stirring was performed for 3 h at a stirring speed of 350 r / min. Then, the mixture was vacuumed for 1 h, sealed and allowed to stand for 2 h, to obtain PVDF solution H;

[0138] The PVDF solution H obtained in the previous step was coated (the coating thickness was 11 μm) on a clean glass plate and then dried at 80° C. for 24 h to obtain a pure polyvinylidene fluoride composite film, which was labeled PVDF.

[0139] Comparative Example 2

[0140] The barium titanate nanoparticles were wet-milled for 5 hours, the ball milling solvent was ethanol, the ball milling speed was 700 r / min, and the liquid after ball milling was dried at 70° C. for 12 hours to obtain barium titanate particles C with a particle size of 80 nm;

[0141] The only difference from Example 2 is that the BT@D filler F in Example 2 is replaced by barium titanate particles C.

[0142] The barium titanate nanoparticle / polyvinylidene fluoride single-layer composite film is recorded as 3 vol.% BP.

[0143] Comparative Example 3

[0144] The only difference from Example 3 is that the BT@D filler F in Example 3 is replaced by barium titanate particles C.

[0145] The single-layer composite film is recorded as 5 vol. % BP composite film.

[0146] Comparative Example 4

[0147] The only difference from Example 4 is that the BT@D filler F in Example 4 is replaced by barium titanate particles C.

[0148] The single-layer composite film is recorded as 7 vol. % BP composite film.

[0149] Comparative Example 5

[0150] The only difference from Example 5 is that the BT@D filler F in Example 5 is replaced by barium titanate particles C.

[0151] The single-layer composite film is recorded as 10 vol. % BP composite film.

[0152] XRD analysis was performed on the barium titanate nanoparticle / polyvinylidene fluoride single-layer composite films obtained in Comparative Examples 2 to 5. The results are as follows: Figure 4 shown.

[0153] Depend on Figure 4 It can be seen that the composite films have obvious PVDF and BaTiO3 phase diffraction peaks, and are composed of two phases; with the increase of BaTiO3 concentration, the BaTiO3 phase diffraction peak of the BP composite films of Comparative Examples 2 to 5 is enhanced, while the PVDF phase diffraction peak first decreases and then increases. At 7 vol.% filling amount, that is, the PVDF phase diffraction peak intensity of the BP composite film obtained in Comparative Example 4 is the smallest.

[0154] XRD analysis was performed on the BDP composite films obtained in Examples 2 to 5. The results are as follows: Figure 5 shown.

[0155] Depend on Figure 5It can be seen that all BDP composite films are mainly composed of BaTiO3 phase and PVDF phase, indicating that BaTiO3@D maintains a good crystal structure in the PVDF matrix. As the filler concentration increases, the diffraction peak intensity of the BaTiO3 phase of the BDP composite films obtained in Examples 2 to 5 increases. Compared with the XRD patterns of the BP composite films obtained in Comparative Examples 2 to 5, no diffraction peak of polydopamine was found in the diffraction spectrum of the BDP composite film, indicating that the D shell layer coated on the BT particles is amorphous.

[0156] The BP composite films obtained in Comparative Examples 3 to 5 and the BDP composite films obtained in Examples 3 to 5 were subjected to SEM analysis. The results are as follows: Figure 6 shown. Figure 6 (a) is the SEM image of the BP composite film in Comparative Examples 3 to 5; Figure 6 (b) is the SEM image of the BDP composite film in Examples 3 to 5.

[0157] Depend on Figure 6 As shown in (a), as the BT concentration increases to 7 vol.%, the filler in the BP composite film obtained in Comparative Example 4 agglomerates, and the agglomeration phenomenon is obvious in Comparative Example 5.

[0158] Depend on Figure 6 As shown in (b), the SEM comparison results of the BDP composite films obtained in Examples 3 to 5 show that when the BT@D filler concentration increases to 10 vol.%, the filler in the BDP composite film obtained in Example 5 only slightly aggregates. This is due to the large surface activity of the polydopamine outer layer, which increases the compatibility of the filler with the PVDF collective material.

[0159] The dielectric constant and dielectric loss of the BP composite films obtained in Comparative Examples 2 to 5 were measured. The results are as follows: Figure 7 shown.

[0160] Depend on Figure 7 It can be seen that the dielectric constant and dielectric loss of the BP composite film have a certain dependence on frequency and filling amount. As the frequency increases, the dielectric constants of all BP composite films decrease in a step-by-step manner, and their dielectric losses first decrease and then increase. As the filling amount increases, the dielectric constants and dielectric losses of the BP composite films obtained in Comparative Examples 2 to 5 increase. Among them, the BP composite film obtained in Comparative Example 4 has a dielectric constant of 13.8 to 18.9 and a dielectric loss of 0.03 to 0.23 in the entire test frequency range, indicating that it has the superior characteristics of high dielectric constant and low dielectric loss.

[0161] The dielectric constant and dielectric loss of the BDP composite films obtained in Examples 2 to 5 were measured. The results are as follows: Figure 8 shown.

[0162] Depend on Figure 8It can be seen that the dielectric constant and dielectric loss of the BDP composite film have a certain dependence on frequency and filling amount. As the frequency increases, the dielectric constants of all BDP composite films decrease in a step-by-step manner, and their dielectric losses first decrease and then increase. As the filling amount increases, the dielectric constants of the BDP composite films obtained in Examples 2 to 5 increase, and their low-frequency dielectric losses first decrease and then increase. Among them, the BDP composite film obtained in Example 4 has a dielectric constant of 14 to 19.5 and a dielectric loss of 0.027 to 0.17 in the entire test frequency range. Compared with the material obtained in Comparative Example 4, the dielectric constant of the BDP composite film increases and the dielectric loss decreases, indicating that the "core-shell" structure BT@D filler can significantly improve the dielectric properties of the PVDF composite film.

[0163] Comparative Example 6

[0164] (1) Same as step (1) of Example 1

[0165] (2) Solution preparation

[0166] a. Under magnetic stirring, 2 g of polyvinylidene fluoride powder was slowly added to a conical flask containing 14 mL of N,N-dimethylformamide solvent at a rate of 80 mg / min. The mixture was magnetically stirred for 3 h at a rate of 350 r / min. The mixture was then vacuumed for 1 h and sealed and allowed to stand for 2 h to obtain PVDF solution H.

[0167] (3) Three-layer nanocomposite film

[0168] The only difference from Example 6 is that solution G is replaced by solution H.

[0169] The obtained three-layer composite film is PVDF-7 vol.% BT@D / PVDF-PVDF, denoted as PVDF-BDP-PVDF, and has a thickness of 30 μm.

[0170] The composite films obtained in Example 6 and Comparative Example 6 were subjected to SEM analysis. The results are as follows: Fig. 9 shown.

[0171] Depend on Fig. 9 It can be seen that the filler BDP is randomly dispersed in the middle layer PVDF substrate and is well combined with the PVDF substrate material; there are obvious stratified interfaces in the two three-layer composite films.

[0172] The dielectric constants of the PVDF film obtained in Comparative Example 1, and the composite films obtained in Example 4, Example 6, and Comparative Example 6 were measured. The results are as follows: Fig.10 shown.

[0173] Depend on Fig.10It can be seen that the dielectric constant of the composite film obtained in Example 6 is 5.6-7.5, which is 6.3%-6.7% lower than that of the PVDF film obtained in Comparative Example 1, which is 6-8. The dielectric constant of the composite film obtained in Comparative Example 6 is 7-9, which is 12.5-16.7% higher than that of the PVDF film. The BDP single-layer composite film obtained in Example 4 has the largest dielectric constant, which is 14-19.3.

[0174] In addition, the composite film obtained in Example 6 has the lowest dielectric loss of 0.03-0.06, which is 50%-65% lower than that of pure PVDF material, proving that the three-layer composite film structure can significantly reduce the dielectric loss on the basis of stabilizing the dielectric constant value.

[0175] The leakage current density of the PVDF film obtained in comparative example 1, the composite film obtained in example 4, example 6 and comparative example 6 was tested, and the results were as follows: Fig.11 shown.

[0176] Depend on Fig.11 It can be seen that the leakage current of the composite film obtained in Comparative Example 6 is the largest, which is (1.4-9.2)×10 -6 A / cm 2 , which is higher than the leakage current of the PVDF film obtained in Comparative Example 1 (0.74-6.73)×10 -6 A / cm 2 The leakage current of the BDP single-layer composite film obtained in Example 4 is lower than that of the PVDF film, which is (0.61-4.61)×10 -6 A / cm 2 In comparison, the leakage current of the composite film obtained in Example 6 is the smallest, which is (0.32~2.94)×10 -6 A / cm 2 , which is 56.3-56.8% lower than that of PVDF material.

[0177] The comparison diagram of the breakdown field strength Weibull distribution of the PVDF film obtained in Comparative Example 1, Example 4, Example 6 and the composite film obtained in Comparative Example 6 is shown in FIG. Fig.12 shown.

[0178] Depend on Fig.12 It can be seen that when the BDP film is compared with the pure PVDF film, the Eb decreases from 283MV / m to 272MV / m. When the PMMA-BDP-PMMA composite film and the PVDF-BDP-PVDF three-layer composite film are compared with the pure PVDF film, the Eb increases by 16.6% and 7.8%, respectively, proving that the PMMA-BDP-PMMA three-layer film structure obtained in Example 6 can significantly improve the breakdown characteristics of the film.

[0179] The electrical tree simulation diagram of the BP composite film obtained in Comparative Example 4 is shown in Fig.13 shown. Fig.13 (a) is the electrical tree simulation diagram of the BP composite film at 16s. Fig.13 (b) is Fig.13 A partial enlarged view of (a).

[0180] Depend on Fig.13 It can be seen that the electrical tree of the BP single-layer composite film develops rapidly, breaking through the filler and PVDF substrate in 16s, and the conductive path of the electrical tree is wide. In particular, the electrical tree development will extend to the inside of the BT nanoparticles, making the BP composite film breakdown faster.

[0181] The electrical tree simulation diagram of the BDP composite film obtained in Example 4 is as follows: Fig.14 shown. Fig.14 (a) is the electrical tree simulation diagram of the BDP composite film at 16s. Fig.14 (b) is Fig.14 A partial enlarged view of (a).

[0182] Depend on Fig.14 It can be seen that the electrical tree breakdown path is narrower than that of the BP single-layer composite film obtained in Comparative Example 4. In addition, the electrical tree development path is blocked by the polydopamine D coating layer, which indicates that the BT filler coated polydopamine D layer has a significant blocking and buffering effect on the development of electrical trees.

[0183] The electrical tree simulation diagram of the composite film obtained in Example 6 is as follows: Fig.15 shown. Fig.15 (a) is the electrical tree simulation diagram of the BDP composite film at 16s. Fig.15 (b) is Fig.15 A partial enlarged view of (a).

[0184] Depend on Fig.15 The electric tree slows down when it enters the middle layer from the outer layer, which is mainly manifested in the electric tree changing from thick to thin. This is attributed to the weakening effect of the linear PMMA polymer outer layer on charge transport and the absorption effect of the electric tree, which reduces the breakdown energy. At the same time, the enlarged image can see the effect of the remaining electric tree being cut off by the polydopamine shell after absorption. This shows the synergistic effect of the PMMA-BDP-PMMA three-layer composite film.

[0185] Fig.16 It is a comparison chart of the difference between the maximum electric displacement polarization value Dm and the residual polarization value Dr of the PVDF film obtained in Comparative Example 1, Example 4, Example 6 and the composite film obtained in Comparative Example 6.

[0186] Depend on Fig.16It can be seen that under the same electric field, the difference between the maximum electric displacement polarization value Dm and the residual polarization value Dr of the composite film is PMMA-BDP-PMMA>PVDF-BDP-PVDF>BDP>PVDF, and the larger the difference, the greater the energy storage density and the better the energy storage characteristics. Therefore, it can be proved that the PMMA-BDP-PMMA three-layer composite film obtained in Example 6 has the best energy storage performance, and the polarization difference Dm-Dr is 6.8μC / cm 2 .

[0187] Fig.17 It is a comparison chart of the released energy density and the charge-discharge efficiency of the PVDF film obtained in Comparative Example 1, Example 4, Example 6 and the composite film obtained in Comparative Example 6.

[0188] Depend on Fig.17 It can be seen that at 325 kV / mm, the PMMA-BDP-PMMA three-layer composite film has the maximum release energy density of 10.4 J / cm 3 , which is 206% higher than pure PVDF, and the energy storage efficiency value is 78.3%, which is 236% higher than pure PVDF. This shows that the PMMA-BDP-PMMA three-layer composite structure with the linear PMMA polymer obtained in Example 6 as the outer layer can comprehensively optimize the energy storage density and efficiency of the material.

[0189] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A film, characterized in that: It comprises polyvinylidene fluoride and barium titanate@polydopamine filler dispersed in the polyvinylidene fluoride; The barium titanate@polydopamine filler is a core-shell structure, wherein the core is barium titanate and the shell is polydopamine.

2. The film according to claim 1, characterized in that The volume fraction of barium titanate@polydopamine filler in the film is 3-10%.

3. The film according to claim 1 or 2, characterized in that The thickness of the polydopamine in the barium titanate@polydopamine filler is 2-10 nm, and the particle size of the barium titanate is below 100 nm.

4. The method for preparing the thin film according to any one of claims 1 to 3, characterized in that: The following steps are involved: The film is obtained by mixing a polyvinylidene fluoride solution with a dispersion of a barium titanate@polydopamine filler, coating the mixture, and drying the mixture.

5. The preparation method according to claim 4, characterized in that: The method for preparing the dispersion of barium titanate@polydopamine filler comprises the following steps: Dispersing barium titanate@polydopamine filler in a polar organic solvent; The dispersion is carried out under cyclic ultrasound and magnetic stirring.

6. The preparation method according to claim 4, characterized in that: The mixing includes adding the polyvinylidene fluoride solution into the dispersion of the barium titanate@polydopamine filler and then performing vacuum treatment and sealing and standing.

7. A composite film, characterized in that: The invention comprises a first PMMA film, a film and a second PMMA film which are stacked in sequence; the film is the film according to any one of claims 1 to 3 or a film prepared by the preparation method according to any one of claims 4 to 6.

8. The method for preparing the composite film according to claim 7, characterized in that: The following steps are involved: Performing a first coating and a first drying on the first PMMA solution to form a first PMMA film; The polyvinylidene fluoride solution is mixed with the dispersion of barium titanate@polydopamine filler, and then coated and dried on the first PMMA film to form a thin film; A second methyl methacrylate solution is second-coated and second-dried on the film to form a second PMMA film, thereby obtaining the composite film.

9. The preparation method according to claim 8, characterized in that: The temperatures of the first drying, drying and second drying are independently 50 to 70° C., and the times are independently 3 to 8 minutes; After the second drying, the method further comprises: performing a third drying on the obtained composite film to obtain the composite film; The temperature of the third drying is 60-80° C. and the time is 20-26 hours.

10. Use of the film according to any one of claims 1 to 3, the film prepared by the preparation method according to claims 4 to 6, the composite film according to claim 7 or the composite film prepared by the preparation method according to any one of claims 8 to 9 in energy storage capacitors.